1984
DOI: 10.1007/bf00217300
|View full text |Cite
|
Sign up to set email alerts
|

Somatostatin in the brain and the pituitary of some teleosts

Abstract: Immunocytochemical investigations show that somatostatin (SRIF)-like immunoreactive material is present in the brain and the pituitary of nine different species of teleosts. In the brain, immunoreactive perikarya and fibers are observed in the preoptic periventricular nucleus, the entopeduncular nucleus, the anterior periventricular nucleus, and the nucleus lateralis tuberis. In the pituitary, SRIF-like-immunoreactive fibers occur in the proximal pars distalis (PPD), which contains the growth hormone (GH)-secr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1989
1989
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…In the European eel, SRIH-14 has been isolated and sequenced from the pancreas [27]; SRIH immunoreactive perikarya were observed in the brain, and fibers were shown in the pituitary on the basal lamina along GH cells [28]. …”
Section: Discussionmentioning
confidence: 99%
“…In the European eel, SRIH-14 has been isolated and sequenced from the pancreas [27]; SRIH immunoreactive perikarya were observed in the brain, and fibers were shown in the pituitary on the basal lamina along GH cells [28]. …”
Section: Discussionmentioning
confidence: 99%
“…The functional role of SOM in the control of GH secretion described for fish (Marchant et al, 1989; Lin et al, 1993) was related to the direct projection of SOM‐ir cells to the hypophysis (Kah et al, 1982; Olivereau et al, 1984; Batten et al, 1985; Grau et al, 1985; Moons et al, 1989), as was also suggested for anurans (LaquerriĂšre et al, 1989). In contrast, urodeles and gymnophionans possess the intense SOM‐ir innervation of the median eminence and, most likely, carry out their role through the portal system as in amniotes (Dubois et al, 1974; Pelletier et al, 1974; Elde and Parsons, 1975; Epelbaum et al, 1977; Palkovits et al, 1980, 1982; Fasolo and Gaudino, 1982; Johansson et al, 1984; Alponti et al, 2006).…”
Section: Discussionmentioning
confidence: 74%
“…Although it is not the aim of the present study to deal extensively with the detailed distribution of SOM in other vertebrates, some comments will be made when needed to assess common vs. specific features of amphibians and, in particular, of Dermophis . For detailed information about the distribution of SOM immunoreactivity, the reader is referred to the mapping studies in cyclostomes (Nozaki and Gorbman, 1983; Wright, 1986; Yåñez et al, 1992), fish (Oliverau et al, 1984; Grau et al, 1985; Bonn and Köning, 1989; Chiba et al, 1989; Meurling and RodrĂ­guez, 1990; Sas and Maler, 1991; Becerra et al, 1995; Vallarino et al, 1997; Trabucchi et al, 2002), reptiles (Fasolo and Gaudino, 1982; Bear and Ebner, 1983; Weindl et al, 1984; Alponti et al, 2006), birds (Shiosaka et al, 1981; Takatsuki et al, 1981; BlĂ€hser, 1984; Fontanesi et al, 1993; Trabucchi et al, 2003), and mammals (Elde and Parsons, 1975; Hoffman and Hayes, 1979; Beal et al, 1983; Johansson et al, 1984; Vincent et al, 1985; Cotter and Laemle, 1987; Desjardins and Parent, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have revealed mammalian-like hypophyseal portal systems in other teleost species (Baskaran and Sathyanesan, 1992). Teleost GRF-and SS-hypothalamic neurosecretory pathways have been identified by immunohistochemistry (Pan, Liu and Bancroft, 1985;Marivoet, Moons and Vandesande, 1988;Olivereau et al, 1984). Both human and a recently purified carp GRF stimulate OH release in vitro (Luo et al, 1990;Le Bail et al, 1991;Vaughan et al, 1992) and in vivo (Peter et al, 1984).…”
Section: The Regulation Of Growth Hormonementioning
confidence: 99%